An investigation into stress response axis, serotonin system and adaptive immunity in depression : a focus on early life adversity and epigenetic mechanisms - Farrell, Chloe Maura (Trinity College. Institute of Neuroscience, 2017)
Major depressive disorder (MDD) is a debilitating psychiatric illness that affects at least 350 million individuals worldwide. Despite its high prevalence rate and its large global disease burden, the biological mechanisms leading to its presentation remain largely unknown. Evidence suggests that alterations reported in physiological systems implicated in the underlying pathogenesis of depression may be mediated, to an extent, via epigenetic mechanisms. It is believed that a large contributor to epigenetic alterations is exposure to early life adversity (ELA), which is of great interest given the high rates of childhood trauma reported by individuals suffering with depression. Research has reported that depressed patients are frequently characterised by a hypercortisolemic state which is believed to be the result of a decrease in the inhibition of hypothalamic-pituitary-adrenal (HPA) axis activity, mediated by increases in DNA methylation at the glucocorticoid receptor/nuclear receptor subfamily 3, group C, member 1 (GR/NR3C1) gene. In accordance with these hypotheses, in this thesis, the assessment of HPA axis activity in a cohort consisting of depressed patients and healthy controls, measured by cortisol concentrations and dynamics, revealed increased morning cortisol concentrations and decreased morning cortisol reactivity in the depressed group. These increased morning cortisol concentrations were associated with both DNA methylation increases at the NR3C1 promoter and decreased GR gene expression. Methylation at sites within the NR3C1 gene were strongly associated with the severity of emotional abuse experienced in childhood, which is in accordance with the literature. Additionally, a similar DNA methylation profile was observed in an independent cohort of babies at six months postpartum. It was revealed that babies born to women who were clinically depressed during pregnancy had increases in DNA methylation at the NR3C1 promoter, compared to babies born to women with no history of psychiatric illness. The degree of DNA methylation at the NR3C1 promoter in babies at six months was strongly associated with a decrease in stress reactivity. Taken together, the findings from this group of studies provide strong evidence for adversity-driven DNA methylation changes at the glucocorticoid receptor gene in depression that are associated with altered HPA axis function. Alterations in serotonin (5-HT) neurotransmission, as a consequence of tryptophan depletion and/or serotonin transporter (5-HTT) dysregulation in the brain, are hypothesised to be another mechanism that contributes to an episode of depression. Epigenetic changes at the gene for the serotonin transporter, solute carrier family 6 member 4 (SLC6A4), have been hypothesised to mediate changes in 5-HTT function. Sitespecific SLC6A4 promoter DNA methylation was significantly decreased in depressed patients. Tryptophan concentrations were also significantly lower in the depressed, compared to the control group. Furthermore, decreases in DNA methylation at the SLC6A4 promoter were associated with increased morning cortisol measures when examining the entire cohort and depressed cohort separately. This inverse relationship between increases in HPA axis activity and reduced 5-HT function, as found in my study, supports the idea of a functional relationship between increased HPA axis output and reduced 5-HT neurotransmission in depression. The relative contribution of the adaptive immune system was also investigated through the assessment of DNA methylation levels at a CG site, cg06164961, in the CD3E gene and its association with the expression of T cell surface glycoproteins. Significant increases in DNA methylation at this site, which were highly associated with reduced gene expression, were observed in depression, with the most profound increases present in depressed patients with a history of adversity. Furthermore, it was revealed that the degree of DNA methylation at the CD3E gene was highly associated with decreases in circulating tryptophan concentrations; providing a novel mechanism to explain the complex interplay between 5-HT neurotransmission and adaptive immune system alterations in depression. Overall, this thesis supports a role for dysregulated stress response, 5-HT and adaptive immune systems, mediated via epigenetic mechanisms, in the aetiology of depression. The findings suggest that the stress and adaptive immune systems particularly may change over time in depressed individuals with a history of childhood adversity, and that these changes may be mediated by epigenetic modifications. On the other hand, epigenetic findings relating to alterations in the 5-HT system would appear to be related more so to the depressed state. The findings of this thesis highlight the complex interactions, spanning from the epigenetic through to the systems level, that occur between these three physiological systems implicated in the pathophysiology of depression and emphasize the need for future studies to investigate the interplay of these systems, taking exposure to early life adversity into account. Major depressive disorder (MDD) is a debilitating psychiatric illness that affects at least 350 million individuals worldwide. Despite its high prevalence rate and its large global disease burden, the biological mechanisms leading to its presentation remain largely unknown. Evidence suggests that alterations reported in physiological systems implicated in the underlying pathogenesis of depression may be mediated, to an extent, via epigenetic mechanisms. It is believed that a large contributor to epigenetic alterations is exposure to early life adversity (ELA), which is of great interest given the high rates of childhood trauma reported by individuals suffering with depression. Research has reported that depressed patients are frequently characterised by a hypercortisolemic state which is believed to be the result of a decrease in the inhibition of hypothalamic-pituitary-adrenal (HPA) axis activity, mediated by increases in DNA methylation at the glucocorticoid receptor/nuclear receptor subfamily 3, group C, member 1 (GR/NR3C1) gene. In accordance with these hypotheses, in this thesis, the assessment of HPA axis activity in a cohort consisting of depressed patients and healthy controls, measured by cortisol concentrations and dynamics, revealed increased morning cortisol concentrations and decreased morning cortisol reactivity in the depressed group. These increased morning cortisol concentrations were associated with both DNA methylation increases at the NR3C1 promoter and decreased GR gene expression. Methylation at sites within the NR3C1 gene were strongly associated with the severity of emotional abuse experienced in childhood, which is in accordance with the literature. Additionally, a similar DNA methylation profile was observed in an independent cohort of babies at six months postpartum. It was revealed that babies born to women who were clinically depressed during pregnancy had increases in DNA methylation at the NR3C1 promoter, compared to babies born to women with no history of psychiatric illness. The degree of DNA methylation at the NR3C1 promoter in babies at six months was strongly associated with a decrease in stress reactivity. Taken together, the findings from this group of studies provide strong evidence for adversity-driven DNA methylation changes at the glucocorticoid receptor gene in depression that are associated with altered HPA axis function. Alterations in serotonin (5-HT) neurotransmission, as a consequence of tryptophan depletion and/or serotonin transporter (5-HTT) dysregulation in the brain, are hypothesised to be another mechanism that contributes to an episode of depression. Epigenetic changes at the gene for the serotonin transporter, solute carrier family 6 member 4 (SLC6A4), have been hypothesised to mediate changes in 5-HTT function. Sitespecific SLC6A4 promoter DNA methylation was significantly decreased in depressed patients. Tryptophan concentrations were also significantly lower in the depressed, compared to the control group. Furthermore, decreases in DNA methylation at the SLC6A4 promoter were associated with increased morning cortisol measures when examining the entire cohort and depressed cohort separately. This inverse relationship between increases in HPA axis activity and reduced 5-HT function, as found in my study, supports the idea of a functional relationship between increased HPA axis output and reduced 5-HT neurotransmission in depression. The relative contribution of the adaptive immune system was also investigated through the assessment of DNA methylation levels at a CG site, cg06164961, in the CD3E gene and its association with the expression of T cell surface glycoproteins. Significant increases in DNA methylation at this site, which were highly associated with reduced gene expression, were observed in depression, with the most profound increases present in depressed patients with a history of adversity. Furthermore, it was revealed that the degree of DNA methylation at the CD3E gene was highly associated with decreases in circulating tryptophan concentrations; providing a novel mechanism to explain the complex interplay between 5-HT neurotransmission and adaptive immune system alterations in depression. Overall, this thesis supports a role for dysregulated stress response, 5-HT and adaptive immune systems, mediated via epigenetic mechanisms, in the aetiology of depression. The findings suggest that the stress and adaptive immune systems particularly may change over time in depressed individuals with a history of childhood adversity, and that these changes may be mediated by epigenetic modifications. On the other hand, epigenetic findings relating to alterations in the 5-HT system would appear to be related more so to the depressed state. The findings of this thesis highlight the complex interactions, spanning from the epigenetic through to the systems level, that occur between these three physiological systems implicated in the pathophysiology of depression and emphasize the need for future studies to investigate the interplay of these systems, taking exposure to early life adversity into account. Major depressive disorder (MDD) is a debilitating psychiatric illness that affects at least 350 million individuals worldwide. Despite its high prevalence rate and its large global disease burden, the biological mechanisms leading to its presentation remain largely unknown. Evidence suggests that alterations reported in physiological systems implicated in the underlying pathogenesis of depression may be mediated, to an extent, via epigenetic mechanisms. It is believed that a large contributor to epigenetic alterations is exposure to early life adversity (ELA), which is of great interest given the high rates of childhood trauma reported by individuals suffering with depression. Research has reported that depressed patients are frequently characterised by a hypercortisolemic state which is believed to be the result of a decrease in the inhibition of hypothalamic-pituitary-adrenal (HPA) axis activity, mediated by increases in DNA methylation at the glucocorticoid receptor/nuclear receptor subfamily 3, group C, member 1 (GR/NR3C1) gene. In accordance with these hypotheses, in this thesis, the assessment of HPA axis activity in a cohort consisting of depressed patients and healthy controls, measured by cortisol concentrations and dynamics, revealed increased morning cortisol concentrations and decreased morning cortisol reactivity in the depressed group. These increased morning cortisol concentrations were associated with both DNA methylation increases at the NR3C1 promoter and decreased GR gene expression. Methylation at sites within the NR3C1 gene were strongly associated with the severity of emotional abuse experienced in childhood, which is in accordance with the literature. Additionally, a similar DNA methylation profile was observed in an independent cohort of babies at six months postpartum. It was revealed that babies born to women who were clinically depressed during pregnancy had increases in DNA methylation at the NR3C1 promoter, compared to babies born to women with no history of psychiatric illness. The degree of DNA methylation at the NR3C1 promoter in babies at six months was strongly associated with a decrease in stress reactivity. Taken together, the findings from this group of studies provide strong evidence for adversity-driven DNA methylation changes at the glucocorticoid receptor gene in depression that are associated with altered HPA axis function. Alterations in serotonin (5-HT) neurotransmission, as a consequence of tryptophan depletion and/or serotonin transporter (5-HTT) dysregulation in the brain, are hypothesised to be another mechanism that contributes to an episode of depression. Epigenetic changes at the gene for the serotonin transporter, solute carrier family 6 member 4 (SLC6A4), have been hypothesised to mediate changes in 5-HTT function. Sitespecific SLC6A4 promoter DNA methylation was significantly decreased in depressed patients. Tryptophan concentrations were also significantly lower in the depressed, compared to the control group. Furthermore, decreases in DNA methylation at the SLC6A4 promoter were associated with increased morning cortisol measures when examining the entire cohort and depressed cohort separately. This inverse relationship between increases in HPA axis activity and reduced 5-HT function, as found in my study, supports the idea of a functional relationship between increased HPA axis output and reduced 5-HT neurotransmission in depression. The relative contribution of the adaptive immune system was also investigated through the assessment of DNA methylation levels at a CG site, cg06164961, in the CD3E gene and its association with the expression of T cell surface glycoproteins. Significant increases in DNA methylation at this site, which were highly associated with reduced gene expression, were observed in depression, with the most profound increases present in depressed patients with a history of adversity. Furthermore, it was revealed that the degree of DNA methylation at the CD3E gene was highly associated with decreases in circulating tryptophan concentrations; providing a novel mechanism to explain the complex interplay between 5-HT neurotransmission and adaptive immune system alterations in depression. Overall, this thesis supports a role for dysregulated stress response, 5-HT and adaptive immune systems, mediated via epigenetic mechanisms, in the aetiology of depression. The findings suggest that the stress and adaptive immune systems particularly may change over time in depressed individuals with a history of childhood adversity, and that these changes may be mediated by epigenetic modifications. On the other hand, epigenetic findings relating to alterations in the 5-HT system would appear to be related more so to the depressed state. The findings of this thesis highlight the complex interactions, spanning from the epigenetic through to the systems level, that occur between these three physiological systems implicated in the pathophysiology of depression and emphasize the need for future studies to investigate the interplay of these systems, taking exposure to early life adversity into account.
Keywords: Neuroscience, Ph.D.; Ph.D. Trinity College Dublin